(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article scientifically and theoretically analyzes the problems of forming and developing media competence in preschool students in a digital educational environment. The content of the concept of media competence, its structural components and pedagogical conditions are clarified. The study substantiates that media information based on children’s literature is an effective tool for developing critical thinking, analytical approach and creative competencies in students. It also highlights the possibilities of improving the professional training of future preschool teachers by integrating media education elements into the educational process.